How Spiromesifen affects some biological parameters and switching behavior of predatory mite Amblyseius swirskii (Acari: Phytoseiidae) when feeding on different ratios of mixed preys - Parvin Asadi; Amin Sedaratian-Jahromi; Mojtaba Ghane-Jahromi; Mostafa Haghani (Persian Journal of Acarology)
Two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae) and silverleaf whitefly, Bemisia tabaci (Gennadius) (Hem.: Aleyrodidae) are among the most destructive pests under greenhouse conditions which is primirarily countered using chemical pesticides. Due to insecticidal and acaricidal effectiveness of Spiromesifen (Oberon®), agricultural producers extensively used this chemical to control both whitefly and spider mite populations. In the present study, effects of recommended concentration of Spiromesifen on some biological and behavioral attributes of predatory mite Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) feeding on different ratios of two-spotted spider mite and silverleaf whitefly were investigated. Different treatments were defined as 1 (150 immature stages of mite + 0 immature stages of whitefly), 2 (120 mite + 30 whitefly), 3 (90 mite + 60 whitefly), 4 (75 mite + 75 whitefly), 5 (60 mite + 90 whitefly), 6 (30 mite + 120 whitefly) and 7 (0 mite + 150 whitefly). According to the results, mortality percentage of adult individuals was not significantly affected by different ratios of prey. With increasing ratio of preys tested in experimental arena, feeding activity of predatory mite on both preys was increased. However, in the case of T. urtice, linear relation observed between the initial number of mite offered and number of mite eaten was more significant. Reproductive responses of female predators to different ratios of mixed preys had no specified trend. Furthermore, switching behavior was not detected in female predators. Our results have considerable role for increasing biological efficacy of A. swirskii in integrated management programs of different pests.